2018
DOI: 10.3390/polym10040438
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Use of Microbial Cellulose as a Biocarrier for 1,3-Dihydroxy-2-Propanone and Its Potential Application in Industry

Abstract: Can microbial cellulose (MC) be used as a bio-carrier for 1,3-dihydroxy-2-propanone (DHA)? The aim of this study was to examine the possibility of using MC as a biomaterial for DHA transferring into the stratum corneum and inducing changes in skin color. The MC patches were obtained from Gluconacetobacter xylinus strain and incubated in solutions with various concentrations of DHA (g·L−1: 20; 50; 80; 110) at 22 °C for 24 h. Afterwards; the patches were applied onto the skin for 15, 30, or 60 min. Skin color ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Main biomedical uses include supports as substitute artificial skin, hemostatic materials, wound healing scaffolds, and controlled drug delivery (Pavaloiu et al, 2014; Picheth et al, 2017). Recently very interestingly insights were obtained using BC as a biocarrier of dihydroxyacetone, in masking the symptoms of vitiligo by providing skin pigmentation (Stasiak and Płoska, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Main biomedical uses include supports as substitute artificial skin, hemostatic materials, wound healing scaffolds, and controlled drug delivery (Pavaloiu et al, 2014; Picheth et al, 2017). Recently very interestingly insights were obtained using BC as a biocarrier of dihydroxyacetone, in masking the symptoms of vitiligo by providing skin pigmentation (Stasiak and Płoska, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, BNC was used not only as the support of the bee venom active components but also as emulsifier and thickener, in the form of nanofiber filaments, of the water-soluble bee venom, replacing the traditional chemical thickeners used in these formulations [ 109 ]. The use of BNC membranes as a carrier was also evaluated for 1,3-dihydroxy-2-propanone (DHA), which is widely used in cosmetics as an active ingredient in self-tanning products [ 110 ]. BNC membranes were impregnated with different DHA concentrations and afterwards tested on skin.…”
Section: Application Of Bacterial Nanocellulose In Cosmeticsmentioning
confidence: 99%
“…As concluded, the method requires improvement, but it demonstrated the potentiality of BNC as a carrier of DHA with the advantage of having the ability of being shaped accordingly to the skin surface on which it will be applied. Therefore, this work opens the possibility of BNC being applied in personalized patches to mask vitiligo symptoms or in self-tanning masks that may be enriched with other active ingredients (e.g., anti-aging compounds) [ 110 ]. In another study, Pacheco et al [ 96 ] also demonstrated the potential of BNC as a sustainable alternative vehicle for cosmetic actives by investigating the incorporation of two formulations into BNC: the vegetable extract mask (VEM) consisting of a moisturizing formulation based on Hidroviton ® (moisturizing agent) and plant extracts (oat and rosemary) and the other composed by a propolis extract and poly(propylene glycol) (PEG), which is identified as a propolis extract mask (PEM).…”
Section: Application Of Bacterial Nanocellulose In Cosmeticsmentioning
confidence: 99%
“…Obtained biocellulose films were washed with distilled water, and then incubated in 1% NaOH at 90 • C for 45 min to remove bacterial cells and medium components. After this stage, the films were neutralized with acetic acid and washed with distilled water [37]. The purified BC films were sterilized in distilled water at 121 • C for 20 min.…”
Section: Purification and Preparation Of Biocellulose Discsmentioning
confidence: 99%